Do Local Protestant Values Affect Corporate Cash Holdings? - Hu, Huajing (Journal of business ethics, 2019)
This study examines how local Protestant belief, as one type of social norms, affects corporate cash policies. We find that firms located in areas with more Protestants hold less cash reserves. The influence of local Protestant belief on cash holdings is more profound for firms with weak corporate governance and firms with one geographic segment. In addition, we find that the difference in cash deployment is reflected in the difference in firms’ investment and payout policies. Overall, our study shows that local Protestant belief is an important factor in determining corporate cash policies and helps to mitigate the potential free cash flow problem.